REFORMASI LAYANAN SAMEDAY SERVICE PASPOR: INOVASI ATAU DISKRIMINASI? - Andriyanto, Riyan; Haq, Nadia; Rosyan, Adam Nurfaizi (Universitas Diponegoro, 2024)
The policy of same day service passport is a policy innovation implemented by the passport service unit, Directorate General of Immigration, Ministry of Law and Human Rights. This policy is a breakthrough in increasing the speed of passport making services to make it shorter. In its implementation, there has been criticism of this policy, namely that it is expensive and not in accordance with the principles of easy, fast and cheap public services. Therefore, this writing was carried out using a qualitative descriptive method with a literature review (SLR) study approach. To be able to carry out the analysis, this writing uses William Dunn's (1980) policy evaluation theory. The results of the analysis obtained were that five of the six policy evaluation variables were found to be still not optimal in implementing the policy to accelerate passport production. The existence of quite high cost charges means that this is not in accordance with existing service principles. The state in providing services to the community must not seek profit. This policy can satisfy the needs, preferences and values of certain communities, it could even be said that only a small portion of the community because the quota is determined at 30% of the maximum quota each day.